Self-care Practices of Diabetic Patients toward the Prevention of Osteoporosis in Babylon Governorate, Iraq - Wael Sulaiman Sabea (Journal of Global Pharma Technology, 2019)
Background: Diabetic patients with uncontrolled insulin are exposed to a potential risk of osteoporosis because disorder of osteoblast-osteoclast function and confusion in the metabolism of calcium, phosphorus and vitamin "D". Objectives: The aim of the study to determine self-care practices of diabetics about the prevention of osteoporosis. Patients and methods :A cross-sectional design study had conducted in in Babel Governorate/Iraq in Endocrinology and Diabetes Diseases Center from 3rd November 2018 to 10th March 2019.Samples were collected during systematic random technique using a questionnaire form had constructed and developed by a researcher after extensive review of related books and available literature. SPSS was used for statistical analysis in the present study. Results: 420 diabetic patients of type 1 and type 2 had been participated in the study with response rate (96. 99%). Their ages ranged from 15-75 years with a mean and standard deviation of 51.8 ± 13.5 years, 53.4% were female and 46.7% were male. More than half of diabetics were married and the majority (63.3%) were livening urban areas. 26.9% of diabetics were illiterate and type 2 diabetes was accounted for 81.2%; hypertension was calculated for 36.4% while obesity for 35.7% of them. The majority (66.4%) of diabetic patients had illustrated fair score (62-77) towards self-care practices about the prevention of osteoporosis. There was significant correlation (P. value ≤ 0.05) between good self-practices of diabetics toward the prevention of osteoporosis and relating to their adult age group, living in urban areas, employed group, high educational grade, type 1diabetes and insulin intake, family member with diabetes, diabetics with normal body mass index. Conclusions: The current study had concluded that diabetic patients generally had fair grade of self-care practices about the prevention of osteoporosis. Recommendations: The study has been suggested the enforcement of well-organized ceaseless educational courses supported with modern educational technologies for diabetic patients in diabetic centers and conducting studies on large samples of diabetic patients in other governorates in Iraq to determine self-care practices towards the prevention of osteoporosis and as well as to determine the prevalence of osteoporosis among diabetics.Keywords: Diabetic patients, Self-care practices, Prevention, Osteoporosis.